ADDRESSING THE ACHIEVEMENT GAP: STRATEGIES FOR EQUITY IN EDUCATION - Singh, Indira; Reeba Devi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The achievement gap, which reflects disparities in academic performance between groups of students, is a persistent issue in education systems worldwide. This paper explores the factors contributing to the achievement gap and presents strategies for promoting equity in education. By analyzing socioeconomic, racial, and systemic influences, this research identifies effective practices and policies that educators, administrators, and policymakers can implement to close the gap. The aim is to provide a comprehensive understanding of the issue and offer actionable solutions to ensure all students have equal opportunities for academic success.